Contextualising environmental and climate change migration in Uganda - Twinomuhangi, Revocatus; Sseviiri, Hakimu; Kato, Arthur Martin (Routledge, 2023)
ABSTRACT The complex linkage between environment, climate change and migration is increasingly capturing global debate. Uganda faces widespread environmental degradation and high vulnerability to climate change impacts that cause livelihood hardships, inducing human mobility. However, the environment, climate change and migration nexus is not well understood and documented, although advocacy to address the livelihood challenges associated with environmental and climate-induced migrations is on the rise. This paper addresses this knowledge gap and presents findings from a review of literature, complemented by key informant interviews and group discussions conducted in the Karamoja, Mt. Elgon and Teso sub-regions of Uganda. The findings show that some socio-economic hardships that cause migrations like natural resources scarcities (water, pastures and fertile soils), hunger and food insecurity and conflicts are linked to slow-onset processes/events related to environmental degradation, rising temperatures and desertification, compounded by sudden-onset events/disasters including; drought, rainstorms, flooding and landslides, that threaten livelihood security and trigger voluntary and forced migrations. Migration also occurs as a coping strategy to environment and climate shocks and stresses. However, empirical research evidence on the numbers of people who have migrated because of environmental change or climate change is still lacking as more research focus has been on the socio-economic and political drivers of migration. Deeper empirical research that incorporates spatial analyses on how the environmental and climate parameters induce migrations is necessary to provide an evidence base to inform transformative policy processes and actions that address human mobility challenges and build resilient societies in Uganda.
Keywords: Climate change, environmental degradation, livelihoods, displacement, migration